Supported cobalt-based catalyst for Fischer-Tropsch reaction as well as preparation method and application of supported cobalt-based catalyst
The preparation of supported cobalt-based catalysts by compounding composite oxides, molecular sieves and carbon materials has solved the problems of low CO conversion and air coal selectivity of existing cobalt-based catalysts, and achieved efficient catalytic performance and long life of Fischer-Tropsch reactions.
Patent Information
- Application Number
- CN202411788745.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-14
AI Technical Summary
When existing cobalt-based catalysts catalyze Fischer-Tropsch reactions, the CO conversion rate and selectivity of the aviation coal fractions are low, the by-product CH4 is high, and the molecular sieve is prone to carbon deposition and inactivation.
Compound oxide, molecular sieve and carbon material are used as support, and mixed with binder and dilute nitric acid melt, and a support-type cobalt-based catalyst is prepared by extruding, drying and calculating.
It achieves high CO conversion rate (greater than 70%), high aviation coal selectivity (greater than 60%) and low inactivation rate, reducing solvent use and wastewater generation, simple process, and facilitates the large-scale synthesis of high-efficiency FTS catalysts.
Smart Images

Figure CN119608232A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of synthesis gas conversion, and in particular to a supported cobalt-based catalyst for Fischer-Tropsch reaction, and a preparation method and application thereof. Background Art
[0002] The use of CO2 to convert into CO or synthesis gas (a mixture of CO and hydrogen) to synthesize jet fuel is currently recognized by the world's aviation industry as a feasible route to reduce CO2 emissions, and is of great significance for the future low-carbon development of the aviation industry. Fischer-Tropsch synthesis (FTS) refers to the conversion of synthesis gas into hydrocarbons under the action of a catalyst. This is a key step in converting non-petroleum-based carbon resources into liquid fuels, and is also a key step in obtaining green jet fuel (C8-C16 liquid hydrocarbon fuels from non-fossil resources). Fischer-Tropsch synthesis has made great progress in the past nearly 100 years.
[0003] The FTS reaction is a complex heterogeneous catalytic system, including a series of parallel and competitive reactions, and its hydrocarbon products follow the Anderson–Schulz–Flory (ASF) distribution law. Therefore, breaking through the ASF distribution limitation and directional synthesis of jet fuel fraction hydrocarbons with a specific carbon number range still faces many technical bottlenecks. At present, industrial FTS catalysts are mainly concentrated in Fe-based and Co-based catalysts. Cobalt-based catalysts are widely used in the Fischer-Tropsch synthesis reaction (FTS) due to their advantages such as higher catalytic reaction activity, high heavy hydrocarbon selectivity, longer life and lower water-gas shift activity.
[0004] Cobalt-based catalysts are mainly supported catalysts. Cobalt-based catalysts in the prior art usually include a carrier, an active component and an additive. The most common carriers are oxides (such as SiO2, Al2O3), molecular sieves and carbon materials.
[0005] CN106669821B discloses a method for preparing a cobalt-based FTS catalyst, including a composite oxide carrier preparation process, an active component and an additive loading process. When the catalyst is used in a slurry bed FTS, it can maintain a high conversion rate and C5 + Product selectivity, but jet fuel selectivity is low.
[0006] CN114797881B discloses a method for preparing a carbon material supported cobalt-based catalyst and its application in CO2 hydrogenation, wherein the carbon material is used as a carrier, metal Co and one or more of the additives Ru, Cr, Re, Zr, and Zn are loaded by an equal volume impregnation method, and then calcined to prepare the catalyst. Although the carbon material supported cobalt-based catalyst has a high selectivity for C5+ hydrocarbons, the selectivity for aviation kerosene is low.
[0007] In recent years, molecular sieves have been introduced into cobalt-based FTS to construct metal-molecular sieve bifunctional catalysts, and good progress has been made in the conversion of synthesis gas to intermediate distillates. At present, the types of metal-molecular sieve FTS catalysts mainly include supported cobalt-based catalysts, physically mixed cobalt-based catalysts, core-shell cobalt-based catalysts, and embedded cobalt-based catalysts. Simple physically mixed Co-based Fischer-Tropsch catalysts avoid the strong interaction between metal and acidic molecular sieves, but simple physical mixing makes it difficult to evenly distribute the components, and it is also difficult to play the coordination role between the bifunctional centers. Noritatsu Tsubaki et al. used mesoporous Y-type molecular sieves to load nano-metal cobalt catalysts and added rare earth metal La as an additive to construct an oxide / molecular sieve bifunctional catalyst. Although this scheme can obtain 72% aviation kerosene selectivity, its CO conversion rate is relatively low (40%), and the bifunctional catalyst requires the addition of relatively expensive rare earth metals (Nature Catalysis 2018, 1, 787-793).
[0008] CN110252389B provides a cobalt-based core-shell catalyst and its preparation method and application. The cobalt-based core-shell catalyst comprises metal cobalt and molecular sieve, with metal cobalt as the core and molecular sieve as the shell; based on the total mass of the catalyst, the content of metal cobalt is 5-30wt%, and the content of molecular sieve is 70-95wt%. In the FTS reaction, the CO conversion rate is as high as 96.1%, and the intermediate distillate oil (C5-C 20 ) up to 80.5%.
[0009] CN104874417B discloses a composite carrier-supported cobalt-based Fischer-Tropsch synthesis catalyst and its preparation and application, wherein the cobalt-based Fischer-Tropsch synthesis catalyst comprises a composite carrier made of a zeolite molecular sieve and an ordered mesoporous material, and an active component cobalt and an auxiliary agent loaded on the composite carrier, wherein the zeolite molecular sieve is one or more of USY, ZSM-5, MCM-22, HY and β zeolite molecular sieve, the ordered mesoporous material is one or more of TiO2, SBA-15, SiC and ZrO2, and the auxiliary agent is one or more of Ni, Zr and Ca. The catalyst has a high CO conversion rate and C5-C 22 Distillate selectivity.
[0010] CN106807439A provides a cobalt-based catalyst and a preparation method thereof, comprising: adding molecular sieve and silicon oxide to a cobalt salt solution and stirring, evaporating the solvent, and drying and calcining to obtain a cobalt-based catalyst. The cobalt-based catalyst has a CO conversion rate of up to 97% and a jet fuel selectivity of 52%.
[0011] The introduction of molecular sieves can effectively improve the selectivity of single products (such as gasoline, aviation kerosene or diesel) in FTS. However, the micropore diffusion limitation inside the molecular sieves makes the intermediate distillate oil further cracked into methane and light hydrocarbons. On the other hand, it also makes the molecular sieve pores easily blocked by carbon deposits and deactivated, greatly reducing the service life of the bifunctional catalyst. In addition, FTS is a highly exothermic reaction, and a large amount of water is generated during the reaction. Since the pore walls of ordered mesoporous materials such as MCM-41 are amorphous, the hydrothermal stability is poor, and the mesoporous structure is easy to collapse. Although La 3+ The exchanged mesoporous Y can be used in the jet fuel fraction produced from syngas, but the price of rare earth La is high and the preparation process of mesoporous Y is complicated, often involving the use of mesoporous templates or post-dealuminization-desiliconization treatment of low-silicon Y, resulting in poor repeatability of molecular sieve performance.
[0012] Therefore, there is an urgent need to develop a new, efficient and inexpensive catalyst that can directly synthesize aviation kerosene fractions through the Fischer-Tropsch reaction with high selectivity and long service life. Summary of the invention
[0013] In view of the shortcomings of the prior art mentioned above, the object of the present invention is to provide a supported cobalt-based catalyst for Fischer-Tropsch reaction and a preparation method and use thereof, so as to solve the technical problems faced by the cobalt-based catalyst in the prior art when catalyzing the Fischer-Tropsch reaction, such as low CO conversion rate and jet fuel fraction selectivity, high by-product CH4 selectivity, and easy carbon deposition and deactivation of molecular sieves.
[0014] To achieve the above objectives and other related objectives, the present invention is achieved through the following technical solutions.
[0015] The present invention provides a method for preparing a supported cobalt-based catalyst for Fischer-Tropsch reaction, comprising the following steps:
[0016] S1. dissolving a cobalt salt and a manganese salt in a solvent to form an impregnation solution;
[0017] S2. After uniformly mixing the composite oxide, molecular sieve, carbon material, binder and the impregnation solution, the supported cobalt-based catalyst is obtained by kneading, extruding and calcining.
[0018] Preferably, the cobalt salt is selected from one or more of cobalt hydroxide, cobalt acetate and cobalt nitrate.
[0019] Preferably, the manganese salt is selected from one or more of manganese acetate, manganese nitrate and manganese chloride. Manganese increases the dispersibility of cobalt and adjusts the electronic properties of cobalt.
[0020] Preferably, the molar ratio of cobalt element to manganese element is 20-45, such as 20-30, 30-35, 35-40, 40-45, and more preferably 30-40.
[0021] Preferably, the solvent is one or more selected from aqueous nitric acid solution, aqueous hydrochloric acid solution and aqueous acetic acid solution. The filtrate in the process of preparing the modified carbon material can be recovered and used as a reagent.
[0022] Preferably, the mass concentration of the solvent is 3-5wt%.
[0023] Preferably, the mass ratio of cobalt in the cobalt salt to the molecular sieve is (20-45):102.5, such as (20-25):102.5, (25-30):102.5, (30-35):102.5, (35-40):102.5, (40-45):102.5, and more preferably (30-40):102.5.
[0024] Preferably, the mass ratio of the composite oxide, the molecular sieve and the carbon material is (1.1-22):102.5:(0.01-2). For example, it may be (1.1-5):102.5:(1.5-2), (5-10):102.5:(1.0-1.5), (5-10):102.5:(0.5-1.0), (10-15):102.5:(0.5-1.0), (15-20):102.5:(0.1-0.5), (20-22):102.5:(0.01-0.1).
[0025] Preferably, the composite oxide comprises titanium oxide and zirconium oxide. The composite oxide is used to improve catalyst stability and reduce deactivation rate.
[0026] More preferably, the mass ratio of the titanium oxide to the zirconium oxide is (5-15):1, such as (5-10):1 or (10-15):1.
[0027] More preferably, the titanium oxide is selected from one or both of fumed titanium dioxide and P25 nano titanium oxide.
[0028] Preferably, the specific surface area of the titanium oxide is 10 to 50 m 2 / g, average pore diameter is 1-10nm, pore volume is 0.1-0.5cm 3 / g.
[0029] Preferably, the specific surface area of the zirconium oxide is 5 to 100 m 2 / g, average pore diameter is 1-10nm, pore volume is 0.1-0.5cm 3 / g.
[0030] Preferably, the silicon-aluminum ratio of the molecular sieve is 20-120, preferably 30-60.
[0031] Preferably, the molecular sieve has a three-dimensional pore structure, the main pore is a twelve-membered ring, and the pore diameter is 0.6-0.75 nm.
[0032] More preferably, the molecular sieve is Beta molecular sieve.
[0033] Preferably, the carbon material is modified by a method of hydrothermal treatment of the carbon material and an aqueous solution of a modification agent. Hydroxyl groups are grafted onto the modified carbon material, which is beneficial for extrusion.
[0034] More preferably, the modifying agent is selected from one or more of hydrogen peroxide, nitric acid, hydrochloric acid and acetic acid.
[0035] More preferably, the carbon material is selected from one or more of carbon nanotubes, mesoporous carbon, graphene and carbon black.
[0036] More preferably, the specific surface area of the carbon nanotubes is 200 to 400 m 2 / g, the average tube diameter is 1-15nm, and the length is 10-50μm.
[0037] More preferably, the specific surface area of the carbon black is 2000 to 3000 m 2 / g, average pore diameter of 0.5-2.5nm, total pore volume of 0.5-2.0cm 3 / g.
[0038] More preferably, the specific surface area of the mesoporous carbon is 500 to 1500 m 2 / g, average pore diameter is 3-10nm, total pore volume is 0.7-1.5cm 3 / g.
[0039] More preferably, the mass concentration of the aqueous solution of the modifying agent is 10 to 50%, preferably 10 to 30%.
[0040] More preferably, the temperature of the hydrothermal treatment is 90-240°C, such as 90-110°C, 110-150°C, 150-200°C, or 200-240°C.
[0041] More preferably, the hydrothermal treatment time is 0.25-12 h, such as 0.25-1 h, 1-3 h, 3-6 h, 6-9 h, 9-12 h.
[0042] More preferably, separation and drying are performed after the hydrothermal treatment. Further preferably, the separation is solid-liquid separation to obtain a filtrate and a solid. Further preferably, the drying is drying the liquid on the surface of the solid.
[0043] Preferably, the binder is selected from one or more of pseudo-boehmite, alumina and aluminum hydroxide.
[0044] Preferably, the mass ratio of the molecular sieve to the binder calculated as Al2O3 is 102.5:(15-55), such as 102.5:(15-28), 102.5:(28-30), 102.5:(30-35), 102.5:(35-40), 102.5:(40-50), 102.5:(50-55).
[0045] Preferably, the mass ratio of the total mass of the composite oxide, the molecular sieve, the carbon material and the binder to the impregnation solution is (0.45-1):1. For example, it may be (0.45-0.5):1, (0.5-1.0):1.
[0046] Preferably, the pH during kneading is controlled to be 4 to 6. More preferably, the pH adjuster is nitric acid.
[0047] Preferably, during the kneading process, the temperature is controlled at 20-35°C.
[0048] Preferably, the kneading time is 0.5 to 2 hours.
[0049] Preferably, during the extrusion process, the extrusion pressure is 8 to 15 MPa.
[0050] Preferably, during the extrusion process, the extrusion speed is 0.1-0.2 m / s.
[0051] Preferably, the extrusion is followed by cutting into strips.
[0052] Preferably, drying is performed before calcination, the drying temperature is 100 to 200° C., and the drying time is 12 to 24 hours.
[0053] Preferably, the calcination atmosphere is an inert atmosphere, such as a nitrogen atmosphere.
[0054] Preferably, the calcination temperature is 350-750° C., and the calcination time is 0.25-10 h.
[0055] The invention also discloses a supported cobalt-based catalyst obtained by the above-mentioned preparation method.
[0056] Preferably, the cross-sectional diameter of the supported cobalt-based catalyst is 1 to 8 mm, such as 1 to 2 mm, 2 to 3 mm, 3 to 4 mm, 4 to 5 mm, 5 to 6 mm, 6 to 7 mm, or 7 to 8 mm.
[0057] Preferably, the specific surface area of the supported cobalt-based catalyst is 100-400 m 2 / g.
[0058] The present invention also discloses the use of the above-mentioned supported cobalt-based catalyst for catalyzing the Fischer-Tropsch reaction.
[0059] Preferably, the Fischer-Tropsch reaction further includes reduction pretreatment.
[0060] More preferably, during the reduction pretreatment, the reducing atmosphere is 10 to 100 vol% H2.
[0061] More preferably, during the reduction pretreatment, the reduction temperature is 250-400°C and the reduction time is 6-16h. For example, the reduction temperature may be 250-300°C, 300-400°C; and the reduction time may be 6-8h, 8-16h.
[0062] Preferably, in the Fischer-Tropsch reaction, the volume ratio of the raw gas H2 to CO is 1:1 to 3:1. For example, it can be 1:1 to 1.5:1, 1.5:1 to 2:1, or 2:1 to 3:1.
[0063] Preferably, the reaction temperature of the Fischer-Tropsch reaction is 200-260°C, such as 200-230°C, 230-260°C.
[0064] Preferably, the reaction pressure of the Fischer-Tropsch reaction is 1-3 MPa, such as 1-2 MPa, 2-3 MPa.
[0065] Preferably, the reaction space velocity of the Fischer-Tropsch reaction is 1500-6000 mL / g cat / h. For example, it can be 1500~3000mL / g cat / h, 3000~6000mL / g cat / h.
[0066] The present invention discloses a supported cobalt-based catalyst for Fischer-Tropsch reaction and a preparation method and use thereof, which have the following beneficial effects:
[0067] The present invention adopts composite oxide, molecular sieve and carbon material as carriers, mixes them with binder and dilute nitric acid solution, and then obtains extruded cobalt-based catalyst in one step after extrusion, drying and roasting. The method is not only simple in process, but also has high mechanical strength of the molded catalyst (extrusion strength is greater than 6N / mm) and good reproducibility of catalytic performance. In addition, the cobalt-based molded catalyst has high CO conversion rate (CO conversion rate is greater than 70%), aviation kerosene fraction selectivity (aviation kerosene selectivity is greater than 60%) and reaction stability (deactivation rate is less than 0.5% / d) in catalytic synthesis gas conversion, and has low CO2 and CH4 selectivity. In addition, the method reduces the use of solvents and the generation of wastewater, has a simple preparation process, and is conducive to the large-scale synthesis of high-efficiency FTS catalysts and their industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] Figure 1 Shown is a photograph of the supported cobalt-based catalyst prepared in Example 1.
[0069] Figure 2 Shown is the powder XRD spectrum of the supported cobalt-based catalyst prepared in Example 1. DETAILED DESCRIPTION
[0070] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0071] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.
[0072] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; it should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in the present invention does not exclude the existence of other devices / apparatuses before or after the combination device / apparatus or the insertion of other devices / apparatuses between these explicitly mentioned two devices / apparatuses, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0073] The following provides specific examples for illustration.
[0074] The sources of the raw materials used in the following examples and comparative examples are as follows:
[0075] Co(NO3)2·6H2O and Mn(NO3)2 solutions (40 wt%) were purchased from Sinopharm Chemical Reagent Co., Ltd., with purities of 99%.
[0076] Concentrated nitric acid was purchased from Sinopharm Chemical Reagent Co., Ltd. with a concentration of 50 wt%.
[0077] Titanium oxide is fumed titanium dioxide, and its crystal forms include anatase and rutile, with a specific surface area of 10 to 30 m 2 / g, average pore diameter is 2-4nm, total pore volume is 0.1-0.3cm 3 / g.
[0078] The specific surface area of zirconia is 40-60m 2 / g, average pore diameter is 2-8nm, total pore volume is 0.1-0.4cm 3 / g.
[0079] The specific surface area of carbon nanotubes is 200-250 m 2 / g, the average tube diameter is 1-7nm, and the length is 10-30 microns; the diameter and length of the carbon nanotubes are measured using a scanning electron microscope.
[0080] The specific surface area of carbon black is 2000~2200m 2 / g, average pore diameter is 1-2nm, total pore volume is 0.7~1.5cm 3 / g.
[0081] Beta molecular sieve (SiO2 / Al2O3=40) was purchased from Nankai Molecular Sieve Factory with a purity of >90%.
[0082] Pseudo-boehmite was purchased from Aluminum Corporation of China Shandong Branch with a purity of 70% and an Al2O3 content of 68.6wt%.
[0083] The specific surface area and pore structure of titanium oxide, zirconium oxide and carbon nanotubes were measured using a Micromeritics ASAP 2000 physical adsorption instrument. During the test, the samples were cooled to -196°C in liquid nitrogen and a low-temperature N2 adsorption-desorption experiment was performed. The specific surface area and pore size were then calculated using the BET equation, and the pore volume was calculated according to the BJH method.
[0084] The physical property parameters of titanium oxide, zirconium oxide, carbon nanotubes and carbon black used in this embodiment are as shown in the above examples, but the protection scope of this application shall be subject to the claims.
[0085] Example 1
[0086] This embodiment provides a specific supported cobalt-based catalyst, and the preparation method is as follows:
[0087] (1) Preparation of modified carbon nanotubes
[0088] 0.25 g of carbon nanotubes and 50 g of 14% nitric acid solution (14 g of concentrated nitric acid + 36 g of water) were added into a 100 mL synthesis reactor, and after hydrothermal treatment at 110° C. for 6 h, the modified carbon nanotubes were obtained by filtration and drying.
[0089] (2) Preparation of impregnation solution
[0090] 190 g of deionized water, 280 g of Co(NO3)2·6H2O and 14.8 g of Mn(NO3)2 solution were added to the nitric acid solution obtained by separation in step (1) to obtain 533 g of impregnation solution, in which the molar ratio of Co to Mn was 3:1.
[0091] (3) Preparation of supported cobalt-based catalysts
[0092] 23.5g of composite oxide, 156.4g of Beta molecular sieve, 0.24g of modified carbon nanotubes and 85.7g of pseudo-boehmite were mixed evenly, added with impregnation solution, and rolled and kneaded in a wheel mill to obtain a clay-like material. The kneading temperature was room temperature and the kneading time was 1h. The clay-like material was transported to an extruder, compressed, extruded and cut into strips. The extrusion pressure was 10MPa and the extrusion speed was 0.1m / s. After drying at 200°C for 12h, it was calcined at 500°C for 6h in a N2 atmosphere to obtain an extruded strip-loaded cobalt-based catalyst with a cross-sectional diameter of 3mm.
[0093] Among them, the mass ratio of cobalt in the cobalt salt to the Beta molecular sieve is 37.2:102.5; the mass ratio of Beta molecular sieve to pseudo-boehmite calculated as Al2O3 is 102.5:38.5; the total mass of the composite oxide, Beta molecular sieve and modified carbon nanotubes is 180.2g, and the mass ratio is 15.4:102.5, 0.16; the composite oxide includes titanium oxide and zirconium oxide, and the mass ratio is 10:1; the mass ratio of the total mass of the composite oxide, Beta molecular sieve, modified carbon nanotubes and pseudo-boehmite to the impregnation solution is 0.5:1.
[0094] Application in Fischer-Tropsch reaction:
[0095] The supported cobalt-based catalyst prepared in this example was subjected to Fischer-Tropsch reaction activity evaluation. The results are shown in Table 1. The activity evaluation process is as follows:
[0096] After crushing and sieving the supported cobalt-based catalyst obtained in Example 1, 1.0 g of 40-60 mesh catalyst particles were weighed, the supported cobalt-based catalyst was evenly mixed with an equal volume of 40-60 mesh quartz sand, and then filled into the middle constant temperature area of the fixed bed reactor, and the upper and lower ends of the catalyst were sealed with 8-16 mesh quartz sand.
[0097] Pure H2 was introduced at a rate of 50 mL / min, and the temperature was raised to 300 °C at a rate of 5 °C / min. The reduction was carried out at normal pressure for 8 h. After the reduction was completed, the temperature was lowered to about 200 °C in a reducing atmosphere. The raw gas (including CO, H2 and N2, with corresponding volume proportions of 32%, 64% and 4%, respectively, with N2 as the internal standard) was switched to the reaction temperature of 230 °C at a rate of 5 °C / min, the reaction pressure was 2 MPa, and the reaction space velocity (under standard volume) was 3000 mL / gcat / h.
[0098] The reaction products were collected, and the gaseous products were detected online using a gas chromatograph (Shimadzu GC-2014) equipped with both a thermal conductivity detector and a hydrogen flame ionization detector. The liquid products obtained by the reaction were analyzed offline using another gas chromatograph equipped with a hydrogen flame ionization detector.
[0099] Figure 1 This is a photograph of the supported cobalt-based catalyst prepared in Example 1.
[0100] Figure 2 This is the powder XRD spectrum of the supported cobalt-based catalyst prepared in Example 1. The active component Co in the supported cobalt-based catalyst exists in the form of Co3O4.
[0101] Example 2
[0102] This embodiment provides a specific supported cobalt-based catalyst, and the preparation method is as follows:
[0103] (1) Preparation of modified carbon nanotubes
[0104] The preparation process is the same as that of Example 1.
[0105] (2) Preparation of impregnation solution:
[0106] 210 g of deionized water, 210 g of Co(NO3)2·6H2O and 11.1 g of Mn(NO3)2 solution were added to 48.2 g of the nitric acid solution obtained by separation in step (1) to obtain an impregnation solution, in which the molar ratio of Co to Mn was 3:1.
[0107] (3) Preparation of supported cobalt-based catalysts
[0108] The preparation process is the same as that of Example 1.
[0109] The mass ratio of the total mass of the composite oxide, Beta molecular sieve, modified carbon nanotubes and pseudo-boehmite to the impregnation solution is 0.6:1; and the mass ratio of cobalt in the cobalt salt to the molecular sieve is 27.9:102.5.
[0110] Application in Fischer-Tropsch reaction:
[0111] The supported cobalt-based catalyst prepared in this example was granulated and then subjected to Fischer-Tropsch reaction activity evaluation. The results are shown in Table 2. The activity evaluation process is the same as that in Example 1.
[0112] Example 3
[0113] This embodiment provides a specific supported cobalt-based catalyst, and the preparation method is as follows:
[0114] (1) Preparation of impregnation solution
[0115] 190 g of deionized water, 280 g of Co(NO3)2·6H2O, and 14.8 g of Mn(NO3)2 were added to ** g of nitric acid solution to obtain an impregnation solution, in which the molar ratio of Co to Mn was 3:1.
[0116] (2) Preparation of supported cobalt-based catalysts
[0117] It is basically the same as Example 1, except that carbon nanotubes are used to replace modified carbon nanotubes.
[0118] Application in Fischer-Tropsch reaction:
[0119] The supported cobalt-based catalyst prepared in this example was granulated and then subjected to Fischer-Tropsch reaction activity evaluation. The results are shown in Table 2. The activity evaluation process is the same as that in Example 1.
[0120] Example 4
[0121] The difference between this embodiment and embodiment 1 is that in step (3), the masses of the composite oxide, molecular sieve and modified carbon material are 8.34 g, 171.0 g and 0.83 g respectively, and the mass ratio is 5:102.5:0.5. The rest is the same as embodiment 1.
[0122] Example 5
[0123] This embodiment provides a specific supported cobalt-based catalyst, and the preparation method is as follows:
[0124] (1) Add 2.1 g of carbon black and 50 g of 14% nitric acid solution (14 g of concentrated nitric acid + 36 g of water) into a 100 mL synthesis kettle, and after hydrothermal treatment at 110° C. for 6 h, filter and dry to obtain modified carbon black.
[0125] (2) 190 g of deionized water, 210 g of Co(NO3)2·6H2O, and 8.9 g of Mn(NO3)2 were added to the nitric acid solution obtained by separation in step (1) to obtain 455 g of impregnation solution, in which the molar ratio of Co to Mn was 39.
[0126] (3) 27.3 g of composite oxide, 139.7 g of Beta molecular sieve, 2.0 g of modified carbon black and 102.8 g of pseudo-boehmite were mixed evenly, and the impregnation solution was added. After kneading, extrusion, cutting and drying for 12 h (drying temperature 110 ° C), it was calcined at 500 ° C for 6 h in a N2 atmosphere to obtain an extruded supported cobalt-based catalyst with a cross-sectional diameter of 3 mm.
[0127] Among them, the mass ratio of cobalt in the cobalt salt to the Beta molecular sieve is 31.2:102.5; the mass ratio of Beta molecular sieve to pseudo-boehmite calculated as Al2O3 is 102.5:51.4; the total mass of the composite oxide, Beta molecular sieve and modified carbon black is 169g, and the mass ratio is 20:102.5:1.5; the composite oxide includes titanium oxide and zirconium oxide, and the mass ratio is 15:1; the mass ratio of the total mass of the composite oxide, Beta molecular sieve and modified carbon nanotubes and pseudo-boehmite to the impregnation solution is 0.5:1.
[0128] Comparative Example 1
[0129] This comparative example is a comparative example of Example 1, and the only difference from Example 1 is that in step (3), silicon oxide is used to replace the composite oxide, and the rest of the preparation method is the same as that of Example 1.
[0130] Application in Fischer-Tropsch reaction:
[0131] The supported cobalt-based catalyst prepared in this comparative example was subjected to Fischer-Tropsch reaction activity evaluation. The results are shown in Table 1. The activity evaluation process is the same as that of Example 1.
[0132] Comparative Example 2
[0133] This comparative example is a comparative example of Example 2, and the preparation method is to first prepare the carrier and then load the active component and the auxiliary agent, as follows:
[0134] (1) A dilute nitric acid solution (14 g of concentrated nitric acid + 286 g of water) was mixed evenly with 23.5 g of a composite oxide, 156.4 g of Beta molecular sieve, 0.24 g of modified carbon nanotubes, and 85.7 g of pseudo-boehmite. After kneading, extrusion, cutting, and drying (conditions: 110°C, 12 h), the mixture was calcined in air at 400°C for 8 h to obtain an extruded carrier with a cross-sectional diameter of 3 mm.
[0135] Among them, the total mass of the composite oxide, Beta molecular sieve and modified carbon nanotubes is 180.2g, and the mass ratio is 15.4:102.5, 0.16; the composite oxide includes titanium oxide and zirconium oxide, and the mass ratio is 10:1; the mass ratio of Beta molecular sieve to pseudo-boehmite calculated as Al2O3 is 102.5:38.5.
[0136] (2) 210 g of Co(NO3)2·6H2O, 11.1 g of Mn(NO3)2 and 240 g of water were mixed to prepare 461.1 g of impregnation solution. The impregnation solution was impregnated onto 241 g of an extruded strip-type carrier by an equal volume impregnation method in three times. The carrier was dried at 110°C for 12 h and then calcined at 500°C for 6 h in a N2 atmosphere to obtain an extruded strip-type supported cobalt-based catalyst with a diameter of 3 mm.
[0137] Application in Fischer-Tropsch reaction:
[0138] The supported cobalt-based catalyst prepared in this comparative example was subjected to Fischer-Tropsch reaction activity evaluation. The results are shown in Table 1. The activity evaluation process is the same as that of Example 1.
[0139] Comparative Examples 3 to 6
[0140] Comparative Examples 3 to 5 are comparative examples of Example 1, and the difference from Example 1 is that in step (3), the added amounts of composite oxide, Beta molecular sieve and modified carbon nanotubes are different from those in Example 1, as shown in Table 1, and the rest are the same as in Example 1.
[0141] Table 1
[0142]
[0143] The supported cobalt-based catalysts prepared in Examples 1 to 5 and Comparative Examples 1 to 6 were tested for extrusion strength. The test results are shown in Table 2. The test method is as follows: According to the ASTM D6175-03 (2013) standard, a side compression strength tester (produced by SMS, UK, model TA.XT PlusC) was used to test the strength of 5 mm length.
[0144] Table 2
[0145]
[0146]
[0147] Other selectivities refer to those except C1, C8-C 16 The selectivity of hydrocarbon products other than hydrocarbons, including C2-C7 hydrocarbons and C 16+ hydrocarbon.
[0148] From the data in Table 1, we can see that:
[0149] If carbon materials are used to replace modified carbon materials, the extrusion strength will be reduced, and the CO conversion rate and aviation fuel (C8-C 16 ) selectivity decreased, while CH4 and CO2 selectivity increased.
[0150] If the amount of modified carbon material used is too much, the extrusion strength will be too poor, the CO conversion rate and jet fuel selectivity will be reduced, the CH4 and CO2 selectivity will be increased, and the deactivation rate will increase.
[0151] If modified carbon materials are not used, although the extrusion strength is improved, the CO conversion rate and jet fuel selectivity are reduced, the CH4 and CO2 selectivity are improved, and the deactivation rate is increased.
[0152] If the dosage of composite oxide is too much, the extrusion strength and jet fuel selectivity will be greatly reduced, the CO conversion rate will be reduced, and the deactivation rate will increase.
[0153] If composite oxides are not used, CH4 selectivity and deactivation rate are significantly improved, extrusion strength is slightly improved, and jet fuel selectivity is slightly reduced.
[0154] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a supported cobalt-based catalyst for Fischer-Tropsch reaction, characterized in that: The steps include: S1. dissolving a cobalt salt and a manganese salt in a solvent to form an impregnation solution; S2. After uniformly mixing the composite oxide, molecular sieve, carbon material, binder and the impregnation solution, the supported cobalt-based catalyst is obtained by kneading, extruding and calcining.
2. The preparation method according to claim 1, characterized in that: Includes one or more of the following features: The cobalt salt is selected from one or more of cobalt hydroxide, cobalt acetate, and cobalt nitrate; The manganese salt is selected from one or more of manganese acetate, manganese nitrate and manganese chloride; The molar ratio of cobalt element to manganese element is 20 to 45; The solvent is one or more selected from aqueous nitric acid solution, aqueous hydrochloric acid solution and aqueous acetic acid solution; The mass concentration of the solvent is 3-5wt%.
3. The preparation method according to claim 1, characterized in that: Includes one or more of the following features: The mass ratio of cobalt in the cobalt salt to the molecular sieve is (20-45):102.5; The mass ratio of the composite oxide, the molecular sieve and the carbon material is (1.1-22):102.5:(0.01-2); The composite oxide includes titanium oxide and zirconium oxide; The silicon-aluminum ratio of the molecular sieve is 20 to 120; The molecular sieve has a three-dimensional pore structure, the main pore is a twelve-membered ring, and the pore diameter is 0.6 to 0.75 nm; The carbon material is subjected to modification treatment, and the modification method is: the carbon material and an aqueous solution of a modification agent are subjected to hydrothermal treatment; The binder is selected from one or more of pseudo-boehmite, alumina, and aluminum hydroxide; The mass ratio of the molecular sieve to the binder calculated as Al2O3 is 102.5:(15-55); The mass ratio of the total mass of the composite oxide, the molecular sieve, the carbon material and the binder to the mass of the impregnation solution is (0.45-1):
1.
4. The preparation method according to claim 3, characterized in that: Includes one or more of the following features: The mass ratio of the titanium oxide to the zirconium oxide is (5-15):1; The specific surface area of the titanium oxide is 10 to 50 m 2 / g, average pore diameter is 1-10nm, pore volume is 0.1-0.5cm 3 / g; The specific surface area of the zirconium oxide is 5 to 100 m 2 / g, average pore diameter is 1-10nm, pore volume is 0.1-0.5cm 3 / g; The molecular sieve is Beta molecular sieve; The modifying agent is selected from one or more of hydrogen peroxide, nitric acid, hydrochloric acid and acetic acid; The carbon material is selected from one or more of carbon nanotubes, mesoporous carbon, graphene and carbon black; The mass concentration of the aqueous solution of the modifying agent is 10-50%.
5. The preparation method according to claim 1, characterized in that: Includes one or more of the following features: The pH value during kneading is controlled at 4-6; During the kneading process, the temperature is controlled at 20-35°C; During the extrusion process, the extrusion pressure is 8-15 MPa; during the extrusion process, the extrusion speed is 0.1-0.2 m / s; The calcination atmosphere is an inert atmosphere; The calcination temperature is 350-750°C; The calcination time is 0.25-10h.
6. A supported cobalt-based catalyst, characterized in that: The method is described in any one of claims 1 to 5.
7. The supported cobalt-based catalyst according to claim 6, characterized in that The cross-sectional diameter of the supported cobalt-based catalyst is 1 to 8 mm.
8. Use of the supported cobalt-based catalyst according to any one of claims 6 to 7 for catalyzing Fischer-Tropsch reaction.
9. The use according to claim 8, characterized in that Includes one or more of the following technical features: The Fischer-Tropsch reaction also includes reduction pretreatment; In the Fischer-Tropsch reaction, the volume ratio of the raw gas H2 and CO is 1:1 to 3:1; The reaction temperature of the Fischer-Tropsch reaction is 200-260°C; The reaction pressure of the Fischer-Tropsch reaction is 1-3 MPa; The reaction space velocity of the Fischer-Tropsch reaction is 1500-6000 mL / g cat / h.
10. The use according to claim 9, characterized in that During the reduction pretreatment, the reducing atmosphere is 10-100 vol% H2; and / or, during the reduction pretreatment, the reducing temperature is 250-400°C and the reducing time is 6-16h.
Citation Information
Patent Citations
Cobalt-based Fischer-Tropsch synthesis catalyst supported by composite carrier and preparation method and application thereof
CN104874417B
A cobalt-based Fischer-Tropsch synthesis catalyst, its preparation method and application
CN106669821B
Cobalt-base catalyst and preparation method thereof
CN106807439A
A cobalt-based core-shell catalyst, its preparation method and application
CN110252389B
Cited By
Co (at) SP S-1 catalyst and preparation method and application thereof
CN120286057A